2020
DOI: 10.1038/s41598-020-68765-x
|View full text |Cite
|
Sign up to set email alerts
|

Rich essential properties of Si-doped graphene

Abstract: The diverse structural and electronic properties of the Si-adsorbed and-substituted monolayer graphene systems are studied by a complete theoretical framework under the first-principles calculations, including the adatom-diversified geometric structures, the Si-and C-dominated energy bands, the spatial charge densities, variations in the spatial charge densities and the atom-and orbital-projected density of states (DOSs). These critical physical quantities are unified together to display a distinct physical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 93 publications
(89 reference statements)
0
12
0
Order By: Relevance
“…The dimensions of graphene and Si-graphene and of CNT and Si-CNT were the same. Fifty percent of the graphene and CNT carbon atoms have been replaced by silicon atoms . Then, their structures were optimized by the Quantum ESPRESSO software and b3lyp­(6311+,631,321) method.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dimensions of graphene and Si-graphene and of CNT and Si-CNT were the same. Fifty percent of the graphene and CNT carbon atoms have been replaced by silicon atoms . Then, their structures were optimized by the Quantum ESPRESSO software and b3lyp­(6311+,631,321) method.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Fifty percent of the graphene and CNT carbon atoms have been replaced by silicon atoms. 21 Then, their structures were optimized by the Quantum ESPRESSO software and b3lyp(6311+,631,321) method. The molecular structure of the micelle-bound αsynuclein (1XQ8) was extracted from the protein data bank at [https://www.rcsb.org/].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Therefore, many new effects appear in low-dimensional materials, which inspire scientists. There are many low-dimensional materials of interest to scientists, including graphene [1], germanene [2], and silicene materials [3]. All three materials have the same honeycomb hexagonal structure, but they are formed from different elements and have characteristic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that using an external field can change the electronic features of germanene, an external electric field can also widen the band gap of germanene, which makes it possible to have a wide range of applications [6][7][8][9]. The doping of elements into the germanene structure also helps to create new materials, the doping gives the material a variety of properties suitable for applications that meet real needs [10][11][12]. The one-dimensional materials explored here are germanene nanoribbons (GNRs), which have two hydrogen-modified edges.…”
Section: Introductionmentioning
confidence: 99%